Abatement technology of endocrine-disrupting chemicals (EDCs) by means of enhanced coagulation and ozonation for wastewater reuse. (December 2021) - Huang, Yu; Chen, Qiuwen; Wang, Zhiyuan; Yan, Hanlu; Chen, Cheng; Yan, Dandan; Ji, Xiaowen
Abstract: In this study, we have investigated the purification efficiency during enhanced coagulation, ozone oxidation and their combined processes for the removal of trace amounts of EDCs in different DOM matrices. The results indicated that the maximum removal efficiency of EDCs occurred at or near pH 7.0 when measured over a pH range of 4.0–10.0. The addition of natural colloids had a two-part influence. While the floc generated by polyaluminium chloride (PAC) significantly increased in size from 198.0 μm to 290.4 μm with a simultaneous improvement in the removal efficiency of EDCs, the floc size generated by polyferric sulfate (PFS) had no worthwhile change except for a slight decrement. The removal efficiency of EDCs and the decrease in spectral parameters including UVA254, UVA280 and humic-like fluorescence during ozonation processes with and without pre-coagulation were investigated. During the ozonation process, efficient elimination of target EDCs are achieved at low O3 doses (O3 /dissolved organic carbon (DOC) < 0.2) in different water matrices. The pH-titration differential absorbance spectra technique further demonstrated that the high reactivity of O3 to EDCs is owing to their phenolic moieties. In addition, when mgO3 /mgDOC ratio reaches to 0.40, >90% of estrogenic activity was eliminated. In a nutshell, ozonation with pre-coagulation together leads to considerably higher abatement of EDCs and estradiol (E2) equivalent values (EEQ) at the same ozone dosage than ozonation only process for wastewater treatment. Graphical abstract: Image 1 Highlights: The maximum removal of EDCs by PAC and PFS occurred at pH 7.0. Colloids increased the floc size and improved EDCs removal during coagulation. Over 90% of estrogenic activity were eliminated when O3 /DOC reached to 0.40. PH-titration DAS demonstrated the high reactivity between O3 and phenolic EDCs. Pre-coagulation mildly enhanced the removal of EDCs and EEQ during ozonation.